Marketing Strategy for Islamic Banking Sharia Financing - Zadur Ali Ahmed (Akademi Sertifikasi Profesi Internasional, 2024)
Islamic banking currently offers business loans under Sharia-compliant strategies. Like conventional banks, Sharia Banks, as primary institutions in Sharia People's Business Loans, must exhibit prudence in managing People's Business Credit funds to avert detrimental financing results. This study seeks marketing strategies for Sharia-compliant micro, small, and medium firms via the Participatory Action Research (PAR) approach. Two marketing strategies exist: traditional and digital, both utilizing the 5Cs—Character, Capacity, Capital, Economic Conditions, and Collateral—to assess the feasibility of client engagement. This study, employing the Strengths, Weaknesses, Opportunities, Threats (SWOT) analytical framework, concluded that the strengths and threats surpass the weaknesses and opportunities. The main factor is inadequate knowledge about Islamic finance. This study is noteworthy as it concentrates on the major annual government initiative and the largest Islamic bank in Indonesia. The cyberattack on the Islamic bank's computer infrastructure is exacerbating the difficulties in restoring public trust. The involvement of scholars and students in PAR-based collaborative efforts may provide an alternative method to address difficulties by improving Islamic financial knowledge